2016
DOI: 10.1097/md.0000000000002489
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscess is Associated With Increased Risk of Acute Kidney Injury

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For this cohort study, we used a hospitalization dataset that contains inpatients claims files and a registry of beneficiaries. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this cohort study, we used a hospitalization dataset that contains inpatients claims files and a registry of beneficiaries. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…Univariate and multivariate Cox proportional hazard regression models were used for estimating hazard ratios (HRs) and 95% confidence intervals (CIs) to assess the effects of VUR on the risk of CKD. [ 12 ] The multivariate models were simultaneously adjusted for age, sex, and comorbidities, namely diabetes mellitus, hypertension, kidney infection, hydronephrosis, cystitis, and UTI. SAS 9.4 software (SAS Institute, Cary, NC) was used for data management and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Failure to receive timely and effective treatment may lead to sepsis, septic shock, sepsis-associated acute kidney injury (SA-AKI), and multi-organ failure[ 3 ]. Sung et al [ 4 ] demonstrated that the overall incidence of acute kidney injury (AKI) was 1.51 times higher in an LA cohort than in a non-LA cohort. Therefore, controlling infections earlier, reducing the inflammatory response, regulating immune function, and protecting kidney function in LA-induced sepsis due to LA is particularly important.…”
Section: Introductionmentioning
confidence: 99%